2003
DOI: 10.1108/09604520310506531
|View full text |Cite
|
Sign up to set email alerts
|

Improving satisfaction with bank service offerings: measuring the contribution of each delivery channel

Abstract: This article presents the results of a qualitative study of a Portuguese bank regarding customer use of Internet banking integrated in a multi-channel offering that includes high street branches, telephone banking, and automatic teller machines. The results show that performance evaluation is a key factor influencing channel use. Customers tend to use the different service delivery systems in a complementary way, taking into account their assessment of the advantages and disadvantages of each one. Customer cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 26 publications
1
63
0
1
Order By: Relevance
“…88 Propelled by technological change, one of the key challenges facing Portuguese fi nancial services was to review and re-establish their competitive strategies. 89 Namely, new entrants, new delivery channels, new services and packages resulted in the automation of bank branches, in the depersonalisation of relationships and in the de-skilling of bank manager tasks. Although Portugal traditionally had a preference for face-to-face channels and personal interaction, this is clearly changing.…”
Section: The Portuguese Banking Sectormentioning
confidence: 99%
“…88 Propelled by technological change, one of the key challenges facing Portuguese fi nancial services was to review and re-establish their competitive strategies. 89 Namely, new entrants, new delivery channels, new services and packages resulted in the automation of bank branches, in the depersonalisation of relationships and in the de-skilling of bank manager tasks. Although Portugal traditionally had a preference for face-to-face channels and personal interaction, this is clearly changing.…”
Section: The Portuguese Banking Sectormentioning
confidence: 99%
“…A number of researchers considered ATM, internet banking, telephone/mobile banking as the principal automated service delivery channels (Dabholkar, 1994;Meuter et al, 2000;Szymanski & Hsiech, 2006;Radecki et al, 1997). Dabholkar (1996) concluded that these three major electronic/automated service channels were frequently accessed by the bank customers in combination with each other, which was further considered to be a relationship-building platform (Lans & Colgate, 2003;Patricio et al, 2003;Ramsay & Smith, 1999). In a comparatively recent study Lin and Hsiech (2006) investigated factors that affect customers' perception of service quality within the domain of self-service technologies and identified seven dimensions of automated service quality -functionality, enjoyment, security, assurance, design, convenience and customization.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It has been considered to be a crucial determinant of the intention of the consumers to make use of financial services and hence, its extensive examination in literature (Patricio, Fisk, & Cunha, 2003). Several prior studies showed that poor services lead to bank switching (Garland, 2005).…”
Section: Perceived Service Quality and Behavioral Intentionmentioning
confidence: 99%